Anesthetic Management of a Tracheoesophageal Fistula in a Patient With a Large Uncorrected Aortopulmonary Window: A Case Report. Issue 7 (1st April 2017) - Adler, Adam C.; Steven, James M.; Jolley, Matthew A.
Abstract : Aortopulmonary window is a rare form of congenital heart disease that requires significant anesthetic considerations. Cardiac involvement is a well-known comorbidity identified in patients with tracheoesophageal fistula (TEF). Identification of coexisting lesions, specifically congenital heart disease, is crucial before undergoing repair of a TEF. Understanding the complex physiology and expected changes occurring during the anesthetic and surgical intervention for correction of TEF with a significant unrepaired shunting defect is crucial to prevent hemodynamic instability. We present the anesthetic management of a 1-day-old neonate with a postnatally diagnosed aortopulmonary window for correction of a TEF.